Study the effect of aqueous extract of hot and alcoholic SaadtubersrotundusCyperus on the mammary glands of female rats Immunohistochemical and Biochemical study - Enaya, Hanaa; Salal, Abdul Hadi (Al-Qadisiyah Journal of Pure Science, 2018)
the present study is designed to focuson the effects that can be performed by the alcoholic extract and waterhotfor the planttubersSaadCyperusrotundusinincreasingthegrowth and development of the mammary glands in female rats during the stages of pregnancy and lactation .. it hasshowed expressions of estrogen and progesterone receptorsacleardecreasewhen the animalstreated byalcoholextractandthehot aqueousextractand cases (Pregnancy andlactationAt a time when thetheexpression ofrecipientestrogen and progesterone in pregnant rats during the period (10 days, 20days ( were, strong (+ + + ),Dropped when the animals treated for hot aqueous extract ubers Saad and duration of the pregnancy itself showed a moderate expression (+ +), while showed mammary gland tissue of animals treated alcoholextractweak expression (+)The fabric of the mammary glands of lactating ratswhich treatedbyalcoholextractandhotaqueous extract, it did not show any expression of estrogen and progesterone receptors ( - ) comparedingwithto control (+) either biochemical studiesTestsshowedsignificantlyincreased(p< 05.0) In the level of catalaseandGlutathiontotalsfor the treatment of alcohol andhot aqueous extractand a significant decrease in the level ofMalondialdehydein the serum of rats and situations (pregnancy and lactation ) compared to the control group